Property insurance - a discussion of the importance of suitable insurance cover against loss relating to commercial property - Ariffin, Mohd. Azmi (Penerbit UTM Press, 1981)
There are many problems related to holding commercial property as an Investment. One of the greatest risks is the possibility of total or partial loss by fire or other misfortune. The value of property destroyed each year by some form of damage is immense. The proper insurance of property is therefore of critical importance. This has been tragically illustrated by a number of recent local disasters concerning the loss of property. Insurance policies must therefore be comprehensive and ensure that any loss will be received in some form or other. There are two bases on which property may be insured, namely, Indemnity and Reinstatement. An Indemnity policy ensures that the property owner does not lose from a financial viewpoint following any damage to his property. A reinstatement policy makes provision for the repair or replacement of any damage so that the property is reconstructed in exactly the same manner after the damage has occurred as it existed beforehand. The onus for fixing a suitable value for insurance purposes falls directly on the Insured. The Insurer will calculate the insurance premium on this sum. However, when a claim is made, the insurer will calculate the 'full insurable value' of the property and this is taken as a ceiling value for insurance cover. Also, if the 'full insurable value is higher than the 'Insured value', the Pro Rata Average Clause is generally operated and only a proportion of the claim will be met. This paper explains the bases of both forms of insurance and the methods of assessing 'full insurable value'. It also explains the working of the Pro Rata Average Clause and the special provisions which ought to be incorporated in an insurance policy for property assets. Finally, the paper concludes by emphasising the responsibilities which face the professional property manager/valuer in advising the property owner in the subject area of property insurance, which is growing increasingly complicated and expensive.